Porosity characterization of biodegradable porous poly (L-lactic acid) electrospun nanofibers. (30th November 2017) - Valipouri, Afsaneh; Gharehaghaji, Ali Akbar; Alirezazadeh, Azam; Ravandi, Seyed Abdolkarim Hosseini
Abstract: Poly-L lactic acid (PLLA) is one of the mostly used fibers in biomedical applications as a biodegradable and biocompatible material. Porosity and fiber diameter distribution are governing factors that determine the performance of nanofibers. Present work aims at investigating the process parameters that are affecting porosity and diameter distribution of PLLA nanofibers. PLLA nanofibers were fabricated through electrospinning method using the solution of PLLA polymer/dichloromethane (DCM). Nanofibers with various fiber diameter distribution and porosity were made by changing of process parameters such as spinning distance (5, 10 and 15 cm), voltage (11 and 15 kV), solution concentration (10, 11 and 12 wt%) and feeding rate (0.3, 0.4 and 0.7 ml h −1 ). Image processing techniques (with Matlab R2017), surface analysis (with Mountainsmap7) and diameter distribution analysis (with Measurement software) were used to examine surface morphology of samples. The results showed that the fiber diameter distribution becomes wider with increasing the applied voltage and reducing the spinning distance. In the other hand, coarse fibers possessed larger pores while having irregular and fewer pores in comparison to fine fibers. The most uniform nano-web with high porous nanofibers was attained by the choice of the process parameters at the voltage of 11 kV, spinning distance of 15 cm, feeding rate of 0.4 ml h −1 and solution concentration of 10 wt%.